Аnatomy and morphological characteristics of the leaf blade of rare endemic species Lonicera iliensis Pojark. (Experimental biology, 2016)
The article presents characteristics of anatomical and morphological structure of a rare, endemic species Lonicera iliensis Pojark. The study of the anatomical structure of the leaf blades of young, medium and old generative plant individuals Lonicera iliensis Pojark. was conducted on nine coenopopulations of three populations. The first population of Ili honeysuckle was found in the floodplain of river Ili near village Bakanas in the Balkhash district, Almaty region, the second population – in the floodplain of river Chilik near village Algabas, Raiymbek district, Almaty region, the third population – in the floodplain of the Charyn River in the tract in Aktogai, Raiymbek district, Almaty region. GPS coordinates of Ili honeysuckle populations: first population – N 44045.784/, E 076019.710/, from 351 to 398 m above sea level; second population – N 43012.079/, E 078031.412/, at 1216-1232 m above sea level; third population – N 43012.959/, E 078050.576, at 1142-1156 m above sea level.Comparison of the anatomical structure of the leaf blades of young, medium and old generative plant individuals Lonicera iliensis Pojark. different coenopopulations showed their great similarity. The all individuals are characterized by dorsoventral and multi-layered mesophyll. In the third coenopopulations all populations (№ 3, № 6 and № 9), all individuals have the widest leaf blade. In the medium generative individuals of Lonicera iliensis Pojark. coenopopulations №5 and №8 leaf blades were characterized by largesize. Also, the individuals of number № 5 and № 8 coenopopulations therewere identified the most features of xeromorphic organization.The results complement the data about the biology of insufficiently explored (little-studied) species Lonicera iliensis.
Keywords: Lonicera iliensis Pojark.; epidermis; sclerenchyma; phloem; parenchyma; trichomes; conductive beam.